The use of electronic management elements and their contribution to increase the effectiveness of the functional performance in sports institutions - hamza.charifz,; rabeh.medjadi, (sports creativity, 2025)
This research aims to know the extent of the contribution of electronic management elements to increase the effectiveness of the functional performance of sports institutions in Algeria, the rapid and rapid growth of modern technology is one of the most important challenges faced by sports institutions through the recruitment and modernization of resources, and the performance of employees in sports institutions is also affected in some way or another Factors, given that new developments and the rapid development of information and communication technologies (ICTs) are the main elements that are affected by administrative organization, which is reflected in the performance level. In this study, the descriptive method was used on a sample of 37 employees The most important results of the study indicated that e-management contributes significantly to increasing the effectiveness of job performance in sports institutions. One of the most important proposals is the need to invest more in the latest technology related to human resources management to improve the institution. And human resource in that one.